Smoking, alcohol, and substance use and rates of quitting during pregnancy: is it hard to quit? - Yazici AB; Uslu Yuvaci H; Yazici E; Halimoglu Caliskan E; Cevrioglu AS; Erol A (Dove Medical Press, 2016)
Ahmet Bulent Yazici,1 Hilal Uslu Yuvaci,2 Esra Yazici,3 Ebru Halimoglu Caliskan,4 Arif Serhan Cevrioglu,2 Atila Erol3 1Department of Psychiatry, Training and Research Hospital, 2Faculty of Medicine, Department of Obstetrics and Gynaecology, 3Faculty of Medicine, Department of Psychiatry, 4Department of Obstetrics and Gynaecology, Training and Research Hospital, Sakarya University, Sakarya, Turkey Background: Alcohol and substance use is a major health challenge in Turkey, as it is worldwide. Recently, there has been a rapid increase in the number of females using substances and although usage tends to reduce during pregnancy, it is of critical importance to determine its exact level as substance use negatively impacts on the health of both the mother and infant.  Aim: The aim of the present study was to investigate the frequency of smoking, alcohol, and substance use, and quitting rates during pregnancy.  Method: This study was conducted on pregnant females in Sakarya, Turkey. A total of 1,082 consecutively presenting females who agreed to participate in the study were evaluated. The study team prepared a sociodemographic data form and adapted the “Introduction” section, derived from the Addiction Profile Index, to cover substance use during pregnancy. Results: The substances most frequently used by pregnant females in their previous pregnancies and current pregnancies were cigarettes/tobacco products (11% and 11.8%, respectively), alcohol (0.6% and 0.4%, respectively), and rarely, synthetic cannabinoids (0.3% and 0.2%, respectively). Daily tobacco smokers continued to smoke during pregnancy, with a rate of 42.5%. Based on research into predictors of smoking (cigarettes) in pregnancy, a correlation was found between lifetime smoking and smoking during a previous pregnancy. A similar link was found with respect to alcohol. Conclusion: Cigarettes are the most frequently used substance in pregnancy, and to a lesser extent, alcohol and synthetic cannabinoids, also considered to be risky substances. A high incidence of smoking regularly during pregnancy was found in daily smokers. It is recommended that physicians should sensitively ask pregnant females presenting at clinics about all forms of substance use, including alcohol and synthetic cannabinoids, and to include such questions in their routine enquiries. Keywords: perinatal, psychiatry, addiction, cessation, women, mental, health